Literasi Keagamaan Terhadap Penyesuaian Diri Generasi Z - Safitri, Syiva; Alfiansa, Sendi; Aslamiah; Suhardin; Wahyuningsih, Dwi (Pusat Penelitian dan Pengabdian Masyarakat STIKes Banyuwangi, 2025)
Religious literacy is an important aspect of education for Generation Z to adapt to changes in the world. It is considered a key focus in efforts toward sustainable development. The critical thinking, problem-solving, questioning, and discussion skills gained from religious literacy significantly influence the adaptability of this generation, especially when they must conform to societal norms. This research focuses on Generation Z in the Pondok Kopi sub-district of East Jakarta as the subject of study and examines the environment as the object of research. The aim of this study is to analyze the impact of the relationship between religious literacy and the adaptability of Generation Z, as well as to measure the extent of that influence. A quantitative approach was used, involving 83 samples from Generation Z in Pondok Kopi. Data analysis techniques included prerequisite tests and correlation tests. The results indicate that there is a significant relationship between religious literacy and the adaptability of Generation Z a correlation coefficient value of 0.001, which is lower than 0.005, indicating that H0 is rejected and H1 is accepted. Additionally, the Pearson correlation value of 0.349 demonstrates a positive relationship.